Patient and Family Advisory Councils for Research: Recruiting and Supporting Members From Diverse and Hard-to-Reach Communities. (October 2019) - Harrison, James D.; Anderson, Wendy G.; Fagan, Maureen; Robinson, Edmondo; Schnipper, Jeffrey; Symczak, Gina; Carnie, Martha B.; Hanson, Catherine; Banta, Jim; Chen, Sherry; Duong, Jonathan; Wong, Celene; et al.
Abstract : OBJECTIVE: To describe strategies to recruit and support members from hard-to-reach groups on research-focused Patient and Family Advisory Councils (PFACs). BACKGROUND: Ensuring diverse representation of members of research PFACs is challenging, and few studies have given attention to addressing this problem. METHODS: A qualitative study was conducted using 8 focus groups and 19 interviews with 80 PFAC members and leaders, hospital leaders, and researchers. RESULTS: Recruitment recommendations were: 1) utilizing existing networks; 2) going out to the community; 3) accessing outpatient clinics; and 4) using social media. Strategies to support inclusion were: 1) culturally appropriate communication methods; 2) building a sense of community between PFAC members; 3) equalizing roles between community members/leaders; 4) having a diverse PFAC leadership team; and 5) setting transparent expectations for PFAC membership. CONCLUSION: Increasing the diversity of research PFACs is a priority, and it is important to determine how best to engage groups that have been traditionally underrepresented. Abstract : Supplemental digital content is available in the text.